PENGARUH BAURAN PEMASARAN (4P), BRAND AWARENESS, DAN CONTENT MARKTING TERHADAP LOYALITAS KONSUMEN KAOS CUSTOM PADA PT. DNS MERCH KEDIRI - Rico Jafar Sidiq; Eko Widodo; Diana Ambarwati (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This research aims to determine the influence of the marketing mix (4P), brand awareness, and content marketing on consumer loyalty for custom t-shirts at PT. Dns Merch in Kediri Regency. The research method used is a quantitative method with a descriptive approach. Data collection in this research was conducted through the distribution of questionnaires to consumers of PT. Dns Merch and analyzed using SPSS Version 25. The data analysis techniques used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t Test, F Test, and Coefficient of Determination R2 Test. In the Validity Test, it was found that all question items (X1, X2, X3, and Y) have a significance value of 0.000 < 0.05, indicating that each variable is valid. Then, in the Reliability Test, each variable is deemed reliable as they have a Cronbach’s Alpha value > 0.60. Furthermore, in the t Test, it was found that the marketing mix variables (4P) (X1), brand awareness (X2), and content marketing (X3) have a significance value of 0.000 < 0.05, indicating that these three variables significantly affect consumer loyalty in a partial manner. Lastly, the F Test shows a significance value of 0.000 < 0.05, indicating that the marketing mix (4P), brand awareness, and content marketing simultaneously influence consumer loyalty at PT. Dns Merch in Kediri Regency.